2018
DOI: 10.1590/0034-737x201865010011
|View full text |Cite
|
Sign up to set email alerts
|

Selection of diazotrophic bacteria isolated from wastewater treatment plant sludge at a poultry slaughterhouse for their effect on maize plants

Abstract: The economic and environmental costs of nitrogen fertilization have intensified the search for technologies that reduce mineral fertilization, for example atmospheric nitrogen-fixing (diazotrophic) bacteria inoculation. In this context, the present study addressed the isolation and quantification of diazotrophic bacteria in the sludge from treated wastewater of a poultry slaughterhouse; a description of the bacteria, based on cell and colony morphology; and an assessment of growth and N content of maize plants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Isolates were subcultured on DYGS semi-solid and specific medium, consecutively, for 24 h at 30 ºC, with the purpose of evaluating the morphological characteristics of both colonies and bacterial cells according to Lozada et al (2018). An isolate code was thus assigned to identify the bacteria as follows: the origin of the material used (Root = RO; Aerial part = AP; Rhizosphere = RHI); the culture medium used (JMV, JMVL, NFb, JNFb, LGI and LGI.P); the dilution used (1 = 10 ) and a number to differentiate bacterial strains isolated from the same Petri dish.…”
Section: Morphological Characterization and Gram Coloring Evaluationmentioning
confidence: 99%
“…Isolates were subcultured on DYGS semi-solid and specific medium, consecutively, for 24 h at 30 ºC, with the purpose of evaluating the morphological characteristics of both colonies and bacterial cells according to Lozada et al (2018). An isolate code was thus assigned to identify the bacteria as follows: the origin of the material used (Root = RO; Aerial part = AP; Rhizosphere = RHI); the culture medium used (JMV, JMVL, NFb, JNFb, LGI and LGI.P); the dilution used (1 = 10 ) and a number to differentiate bacterial strains isolated from the same Petri dish.…”
Section: Morphological Characterization and Gram Coloring Evaluationmentioning
confidence: 99%
“…As well as our results, Bunraksa et al (2020) demonstrated a great diversity of microorganisms isolated in the poultry slaughterhouse sludge, and some microorganisms have the effect of synthesizing substances that promote growth in plants. Also reported a great diversity of bacteria isolated in poultry slaughterhouse sludge, some of which have the ability to fix atmospheric N (Lozada et al, 2018).…”
Section: Introductionmentioning
confidence: 99%